2004
DOI: 10.1002/eji.200324829
|View full text |Cite
|
Sign up to set email alerts
|

Frontline: Absence of functional STAT4 activation despite detectable tyrosine phosphorylation induced by murine IFN‐α

Abstract: We previously reported that IL-12, but not IFN-aA/D, induces T helper type (Th) 1 development and STAT4 phosphorylation in murine CD4 + T cells. However, a recent study reported that IFN-aA/D and recombinant murine IFN-aA can induce STAT4 phosphorylation, although more weakly than IL-12, largely in CD8 + rather than CD4 + T cells. That report did not examine Th1 development or directly demonstrate induction of IFN-c by IFN-a. To address these differences, we compared IFN-aA/D, murine IFN-aA, and IL-12 for STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…It has been suggested that the use of different IFN-␣ subtypes could account for this discrepancy. However, Berenson et al (45) recently demonstrated that, although mIFN-␣ (A) was more active than rhIFN-␣ (A/D) at promoting weak STAT4 phosphorylation (as observed by Nguyen et al (16)), neither of these IFN-␣ subtypes was able to induce Th1 commitment within CD4 ϩ T cells, and the present study confirms this observation. In addition, Nguyen et al (16) reported elevated STAT4 phosphorylation in response to IFN-␣␤ in murine CD8…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that the use of different IFN-␣ subtypes could account for this discrepancy. However, Berenson et al (45) recently demonstrated that, although mIFN-␣ (A) was more active than rhIFN-␣ (A/D) at promoting weak STAT4 phosphorylation (as observed by Nguyen et al (16)), neither of these IFN-␣ subtypes was able to induce Th1 commitment within CD4 ϩ T cells, and the present study confirms this observation. In addition, Nguyen et al (16) reported elevated STAT4 phosphorylation in response to IFN-␣␤ in murine CD8…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we determined that the role of STAT1 in Th1 cell trafficking was specific to Th1 cells as Ag-specific Th2 cells traffic normally in STAT1 Ϫ/Ϫ mice. CD4 ϩ T cells from STAT1 Ϫ/Ϫ mice have been shown to differentiate to a Th1 phenotype and secrete IFN-␥ but to a lesser extent than the WT (33). Therefore, we used an adoptive transfer model to isolate the role of STAT1 in Th1 cell trafficking apart from its role in Th1 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For some time, the actions of type I IFN, such as IFN-␣, were thought to differ between the human and murine system. While IFN-␣ was claimed to drive Th1 development in human T cells (8 -10), type I IFN did not drive Th1 development in mouse T cells (11)(12)(13). Type I IFN were thought to induce STAT4 phosphorylation in human T cells, but not murine Th1 cells (14,15).…”
Section: T He Differentiation Of Naive Cd4mentioning
confidence: 99%
“…Type I IFN were thought to induce STAT4 phosphorylation in human T cells, but not murine Th1 cells (14,15). However, it was recently reported that IFN-␣ can activate STAT4 in murine T cells responding to lymphocytic choriomeningitis virus (LCMV) 4 infection (16) or already differentiated Th1 cells (13), although these studies did not demonstrate the ability of IFN-␣ to induce Th1 differentiation. A potential species-specific STAT4 activation by IFN-␣ was proposed to involve a mutation in the murine STAT2 gene that would diminish STAT4 recruitment (15,17).…”
Section: T He Differentiation Of Naive Cd4mentioning
confidence: 99%